Notes on Early Land Plants Today. 71. New synonyms, new names and new combinations in Lejeuneaceae (Marchantiophyta) - Pócs, Tamas; Zhu, Rui-Liang; Reiner-Drehwald, Elena; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2015)
For the coming checklist of hornworts and liverworts (Söderström et al., in press) a few validations, transfers and synonymizations in the family Lejeuneaceae are still required.